A convenient one-pot synthesis of boroxoles from diboronic acid. Issue 39 (27th September 2017) - Lafitte, Guillaume; Kunihiro, Kana; Bonneaud, Céline; Dréan, Bénédicte; Gaigne, Frédéric; Parnet, Véronique; Pierre, Romain; Raffin, Catherine; Vatinel, Rodolphe; Fournier, Jean-François; Musicki, Branislav; Ouvry, Gilles; et al.
Graphical abstract: Highlights: An efficient one-pot process to prepare boroxoles directly from diboronic acid is disclosed. This mild process avoids the necessity of carrying out a halogen-lithium exchange under cryogenic conditions. A diverse range of boroxoles were prepared in acceptable yield with good substrate scope. Abstract: The preparation of the boroxole motif traditionally relies on a 3-step process and the use of n -butyl lithium that can limit substrate scope. Herein during our exploration toward novel RORγ inhibitors, we identified a convenient one-pot preparation of the motif in good yields with good substrate scope.